Transcription Promotes the Interaction of the FAcilitates Chromatin Transactions (FACT) Complex with Nucleosomes in Saccharomyces cerevisiae. Issue 3 (20th September 2018) - Martin, Benjamin J E; Chruscicki, Adam T; Howe, LeAnn J
Abstract: FACT (FAcilitates Chromatin Transactions) is an abundant and conserved complex that is essential for cell viability. FACT binds to highly expressed genes and facilitates transcription while maintaining chromatin structure, but how it is targeted... The FACT (FAcilitates Chromatin Transactions) complex is a conserved complex that maintains chromatin structure on transcriptionally active genes. Consistent with this, FACT is enriched on highly expressed genes, but how it is targeted to these regions is unknown. In vitro, FACT binds destabilized nucleosomes, supporting the hypothesis that FACT is targeted to transcribed chromatin through recognition of RNA polymerase (RNAP)-disrupted nucleosomes. In this study, we used high-resolution analysis of FACT occupancy in Saccharomyces cerevisiae to test this hypothesis. We demonstrate that FACT interacts with nucleosomes in vivo and that its interaction with chromatin is dependent on transcription by any of the three RNAPs. Deep sequencing of micrococcal nuclease-resistant fragments shows that FACT-bound nucleosomes exhibit differing nuclease sensitivity compared to bulk chromatin, consistent with a modified nucleosome structure being the preferred ligand for this complex. Interestingly, a subset of FACT-bound nucleosomes may be "overlapping dinucleosomes, " in which one histone octamer invades the ∼147-bp territory normally occupied by the adjacent nucleosome. While the differing nuclease sensitivity of FACT-bound nucleosomes could also be explained by the demonstrated ability of FACT to alter nucleosome structure, transcription inhibition restores nuclease resistance, suggesting that it is not due to FACT interaction alone. Collectively, these results are consistent with a model in which FACT is targeted to transcribed genes through preferential interaction with RNAP-disrupted nucleosomes.